God’s Words in Dialogue: Dabru Emet, Dei Verbum, Nostra Aetate - Ochs, Peter W. (Studies in Christian-Jewish Relations, 2025)
Celebrating the anniversaries of Dabru Emet and Nostra Aetate, I ask how these urgent documents may best contribute to repairing tension and conflict between Christian and Jewish communities. I celebrate the documents as beacons of hope that warn against the dangers of mutual misunderstanding. But I add a caution: hearing about the dangers is helpful only if Jews and Christians also get instruction in how to recognize, interpret, and respond successfully to such dangers. (I add a technical comparison of two kinds of reasoning: one that offers warnings and one that recommends repairs.) When communities who worship God enter, nevertheless, into religious conflict, then God alone can repair such conflict: God’s word alone instructs each community and how to recognize and contribute to repairing their sources. I turn to Dei Verbum as Vatican II’s manual for locating God’s instructive word in each community’s tradition of receiving and enacting scriptural revelation. But what if each community receives such instruction in conflicting ways? Perhaps repair comes only when God’s word enters into redeeming dialogue with God’s word. Perhaps the Centers on Jewish-Christian Relations may host such a dialogue.